Evolutionary history and climate co-determine the geographical variation in pollination modes of angiosperms in China - Wang, Yunyun; Li, Yichun; Luo, Ao; Lyu, Tong; Freckleton, Robert P.; Dimitrov, Dimitar; Wang, Zhiheng (Global Ecology and BiogeographyGlobal Ecology and Biogeography, 2023)
Abstract Aim Pollination is an essential stage of angiosperm reproduction, and the mode of pollination plays a major role in driving evolutionary and ecological responses of plants to environmental changes. However, the effects of climate, evolutionary history and floral traits (i.e. plant sexual systems) on pollination mode variation remain unclear. Here, we explored the biogeographic patterns in pollination mode frequency and tested the hypothesis that insect pollination prevails in warm humid regions with old floras due to high pollinator dependence, whereas wind pollination is more frequent in arid regions with younger floras and is more strongly associated with dioecy. Location China. Time period Since the Last Glacial Maximum. Major taxa studied Angiosperms. Methods Using data on pollination modes and geographic ranges of 29,719 angiosperm species in China, we mapped the biogeographic pattern of pollination mode frequency. Phylogenetic logistic regressions and generalized linear mixed models were employed to evaluate the relative importance of climate, evolutionary history (represented by phylogenetic conservatism and grid-level mean genus age) and sexual systems on variations in pollination modes across species and space. Results Evolutionary history was the strongest correlate of pollination mode variation across species and space. The proportion of insect-pollinated species was higher in humid regions with old floras, but lower in arid regions with young floras. Evolutionary history and temperature dominated variations in pollination mode frequency in humid areas, while precipitation dominated in arid areas. Climate influenced geographic pattern in pollination mode frequency both directly and indirectly via its effects on species richness and plant sexual systems. Main Conclusions Our results showed that geographic pattern in angiosperm pollination mode frequency is dominated by evolutionary history followed by climate, which extended previous findings of climate-driven mechanisms. Our findings demonstrate the importance to incorporate evolutionary history in understanding the mechanisms underlying the functional biogeography of plant traits.
Keywords: China; climate change; co-evolution; evolutionary history; flowering plants; geographical pattern; pollination mode; sexual system